Proton irradiation and resistivity recovery in stages I & II of pure and carbon-doped Fe - Theodorou, Andreas; Syskaki, M.; Kotsina, Z.; Axiotis, M.; Apostolopoulos, G. (HNPS Advances in Nuclear Physics, 2020)
Pure and C-doped Fe specimens were irradiated with 5 MeV protons at cryogenic temperature at the NCSR-"Demokritos" TANDEM accelerator in order to investigate the interactions between carbon atoms and radiation defects. During the subsequent post-irradiation isochronal annealing up to 180 K the defects start to migrate and interact either mutually or with the C impurities. The defect evolution is observed by in-situ electrical resistivity recovery measurements. Comparison of results from pure and C-doped Fe specimens reveals the effect of C solute atoms on the defect kinetics.